Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles

Comparative proteomics of sugarcane smut fungus- Sporisorium scitamineum unravels dynamic proteomic alterations during the dimorphic transition - Kumaravel, Nalayeni; Ebinezer, Leonard Barnabas; Ashwin, N. M. R.; Franchin, Cinzia; Battisti, Ilaria; Carletti, Paolo; Sundar, Amalraj Ramesh; Masi, Antonio; Malathi, Palaniyandi; Viswanathan, Rasappa; Arrigoni, Giorgio (Journal of Proteomics, 2024)
Life cycle of the dimorphic sugarcane smut fungi, Sporisorium scitamineum , involves recognition and mating of compatible saprophytic yeast -like haploid sporidia (MAT -1 and MAT -2) that upon fusion, develop into infective dikaryotic mycelia. Although the dimorphic transition is intrinsically linked with the pathogenicity and virulence of S. scitamineum , it has never been studied using a proteomic approach. In the present study, an iTRAQ-based comparative proteomic analysis of three distinct stages was carried out. The stages were: the dimorphic transition period - haploid sporidial stage (MAT -1 and MAT -2); the transition phase (24 h post co -culturing (hpc)) and the dikaryotic mycelial stage (48 hpc). Functional categorization of differentially abundant proteins showed that the most altered biological processes were energy production, primary metabolism, especially, carbohydrate, amino acid, fatty acid, followed by translation, post -translation and protein turnover. Several differentially abundant proteins (DAPs), especially in the dikaryotic mycelial stage were predicted as effectors. Taken together, key molecular mechanisms underpinning the dimorphic transition in S. scitamineum at the proteome level were highlighted. The catalogue of stage -specific and dimorphic transition -associated -proteins and potential effectors identified herein represents a list of potential candidates for defective mutant screening to elucidate their functional role in the dimorphic transition and pathogenicity in S. scitamineum . Biological significance: Being the first comparative proteomics analysis of S. scitamineum , this study comprehensively examined three pivotal life cycle stages of the pathogen: the non-pathogenic haploid phase, the transition phase, and the pathogenic dikaryotic mycelial stage. While previous studies have reported the sugarcane and S. scitamineum interactions, this study endeavored to specifically identify the proteins responsible for pathogenicity. By analyzing the proteomic alterations between the haploid and dikaryotic mycelial phases, the study revealed significant changes in metabolic pathway -associated proteins linked to energy production, notably oxidative phosphorylation, and the citrate cycle. Furthermore, this study successfully identified key metabolic pathways that undergo reprogramming during the transition from the non-pathogenic to the pathogenic stage. The study also deciphered the underlying mechanisms driving the morphological and physiological alterations crucial for the S. scitamineum virulence. By studying its life cycle stages, identifying the key metabolic pathways and stage -specific proteins, it provides unprecedented insights into the pathogenicity and potential avenues for intervention. As proteomics continues to advance, such studies pave the way for a deeper understanding of plantpathogen interactions and the development of innovative strategies to mitigate the impact of devastating pathogens like S. scitamineum.
Keywords: dimorphism; fungi; iTRAQ; Smut; Sugarcane; Virulence